Convergence in Government Spending Components in EU15: A Spatial Econometric Perspective - Lena Maleševic Perović; Silvia Golem; Maja Mihaljević Kosor (Amfiteatru Economic Journal, 2016)
This paper contributes to the empirical literature on convergence by applying convergence model to components of government expenditures (by function) in EU15 during 1995-2010, using the data from United Nations Statistics Division. Moreover, we extend the traditional convergence model to allow for spatial correlation between countries in the sample, by estimating spatial autocorrelation (SAC) model for each component of government expenditures. This approach is important in that it provides more efficient coefficients, and offers policy-makers useful information regarding fiscal policies determinants that are attributable to other countries. We find that spatial aspects play an important role for Defence, Health and Education. More precisely, half-life convergence for Defence occurs in 6.37 years, for Health in 3.11 years and for Education in 5 years.
Keywords: C23; H1; H5; O47; 330; convergence; government expenditure by functions; spatial econometrics